2018
DOI: 10.1515/med-2018-0017
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among anesthetists and intensive care physicians

Abstract: AbstractBurnout is a syndrome of depersonalization, emotional exhaustion, and low personal accomplishment. Little is known about burnout in physicians. Our objective was to determine the prevalence of burnout among anesthetists and intensive care physicians, and associations between burnout and personal, as well as professional, characteristics.MethodsIn total, 220 anest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 27 publications
1
58
1
7
Order By: Relevance
“…Moreover, a different type of scale is used for students. 2 In 2017, a survey among Dutch medical professionals found that 13.9% of the participated Dutch dentists reported burnout-related complaints, 19 and also more (para)medical workers 29,30 and medical students 28 than dental hygienists seem to exhibit burnout symptoms. the UBOS-A, UBOS-C and UWES-9 among both dental hygienists and young professionals dental hygienists were fairly consistent with those reported in the Manual.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a different type of scale is used for students. 2 In 2017, a survey among Dutch medical professionals found that 13.9% of the participated Dutch dentists reported burnout-related complaints, 19 and also more (para)medical workers 29,30 and medical students 28 than dental hygienists seem to exhibit burnout symptoms. the UBOS-A, UBOS-C and UWES-9 among both dental hygienists and young professionals dental hygienists were fairly consistent with those reported in the Manual.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some similar associations of predictors with burnout were identified in other occupational studies. Thus, alcohol use was shown to have a positive association with burnout in intensive care physicians [6], community pharmacists [7], prison employees [8], priests [9], and similar association was found in a populations-based sample [10]. Since data on firefighters on such association were not published before, findings from the latter population-based study assume that such association is not specific for firefighters and can be found in many other occupations.…”
Section: Discussionmentioning
confidence: 99%
“…Favorecendo os achados, constataram-se elevados níveis de estresse entre médicos plantonistas especializados em Anestesiologia, sendo que o maior tempo de experiência profissional se correlacionou a índices menores de fadiga emocional, visto que esses profissionais trocam menos de local de trabalho com o passar dos anos (26,27) . Como grande parte da amostra do presente estudo é de médicos sem especialização, justifica a diferença estatística inferior encontrada no domínio do meio ambiente.…”
Section: Discussionunclassified